Selective Disclosure of HIV Status in Egocentric Support Networks of People Living with HIV/AIDS - Zang, Chunpeng (AIDS Behav, 2015)
The objective of this study was to investigate HIV disclosure activities in social support networks of people living with HIV/AIDS (PLWHAs). An egocentric network study was conducted in Nanning, China. A sample of 147 PLWHAs (egos) nominated 922 network members (alters) who would provide egos with social support. All egos disclosed their HIV status to at least one alter in their support networks and 26.5 % disclosed to all alters. Among network alters, 95.7 % of spouse alters, 59.9 % of other family member alters, and 29.7 % of friend alters were aware of egos’ HIV status. PLWHA egos were more likely to disclose their HIV status to their spouse and other family members, frequently-contacted alters, and alters who provided more social support. In addition, older egos and unmarried egos were more likely to disclose their HIV status. The findings indicate that network-based HIV intervention programs should take into consideration selective disclosure in social networks.